ChemInform Abstract: Cu‐Catalyzed Fluorination of Diaryliodonium Salts with KF. Issue 8 (25th February 2014) - Ichiishi, Naoko; Canty, Allan J.; Yates, Brian F.; Sanford, Melanie S.
Abstract Unsymmetrical diaryliodonium tetrafluoroborates having an aryl and a mesityl substituent react with KF in the presence of Cu(II)‐catalysts to give preferentially the corresponding aryl fluorides and only minor amounts of mesityl fluoride.